Pandemia COVID-19 a realizacja funkcji opiekuńczo-wychowawczej w wiejskich rodzinach wielodzietnych – wybrane problemy - Klementowska, Aneta (Wydawnictwo Naukowe EDUsfera. Ewa Jurczyk-Romanowska, 2021)
The article is theoretical and empirical in nature. It raises issues relating to the execution of care-providing and educational functioning in rural multi-child families during the Covid-19 pandemic. On the basis of source literature and legal documents, the family and the multi-child family are characterized, and the functions of the family are presented. The results of a research are demonstrated as conducted in 2021 among parents of rural multi-child families.
Keywords: family; multi-child family; care-providing and educational function; COVID-19 pandemic